2021
DOI: 10.1039/d1ra05688c
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional polymer-derived ceramic nanowires with electrocatalytically active metallic silicide tips as cathode catalysts for Zn–air batteries

Abstract: New intermetallic silicide catalysts for Zn–air batteries facilitate ORR/OER kinetics and deliver peak power densities of 59 mW cm−2 and 1200 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the present work, the lowest ∆E value of 0.89 V was obtained in the case of FeCoNi-CNF catalyst, which is ca. 100 mV higher compared to the ∆E value found in the case of polymer-derived ceramic nanowire catalysts with metallic silicide tips in our previous investigation of RZAB air electrode catalysts [46]. The dual-doped TM Pc functionalized CNT-based materials have shown even better ∆E values (0.76-0.84 V) in recent papers [40,71].…”
Section: Tablementioning
confidence: 60%
See 3 more Smart Citations
“…In the present work, the lowest ∆E value of 0.89 V was obtained in the case of FeCoNi-CNF catalyst, which is ca. 100 mV higher compared to the ∆E value found in the case of polymer-derived ceramic nanowire catalysts with metallic silicide tips in our previous investigation of RZAB air electrode catalysts [46]. The dual-doped TM Pc functionalized CNT-based materials have shown even better ∆E values (0.76-0.84 V) in recent papers [40,71].…”
Section: Tablementioning
confidence: 60%
“…Nevertheless, it should be mentioned that the Zn-electrode area can play a crucial role in the measured P max value, which highlights the necessity to include the comparison curve with commercial PGM catalyst [ 47 , 80 ]. Also, the total discharge curve at 20 mA cm −2 was recorded for primary batteries with Pt-Ru/C and FeCoNi-CNF air electrodes to calculate the specific capacity according to the amount of consumed Zn electrode ( Figure 8 b) [ 46 ]. Specific capacities of 695 and 407 mAh g Zn −1 were obtained for Pt-Ru/C and FeCoNi-CNF, respectively, while the theoretical specific capacity is 820 mAh g Zn −1 [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to synergistic effects between in situ grown CNTs and intermetallic nickel silicides (Ni 31 Si 12 and Ni 2 Si), Ni-containing PDC monoliths exhibited better bifunctional activities than other metal-based PDC composites with respect to both OER and ORR, with a low ΔE value of 1.20 V. Based on their discovery that transition metal nanoparticles can initiate the growth of CNTs within the porous PDCs architecture, the same authors further prepared metal-containing PDC nanowires decorated with intermetallic silicide tips by applying azodicarbonamide (ADA) as an extra foaming agent and increasing the pyrolysis temperature. 152 This ADA is capable of influencing the rheological properties of the preceramic polymer and its decomposition behavior, thereby changing the structure of the PDCs. The electrochemical results demonstrated that all the metal-containing PDCs (Ni/PDC, Co/PDC, and Fe/PDC) performed as excellent ORR/OER bifunctional catalysts.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%